In vivo measurement of conduction velocities in afferent and efferent nerve fibre groups in mice - Steffens, H; Dibaj, P; Schomburg, E. D (Physiological research, 2012)
Electrophysiological investigations in mice, particularly with altered myelination, require reference data of the nerve conduction velocity (CV). CVs of different fibre groups were determined in the hindlimb of anaesthetized adult mice. Differentiation between afferent and efferent fibres was performed by recording at dorsal roots and stimulating at ventral roots, respectively. Correspondingly, recording or stimulation was performed at peripheral hindlimb nerves. Stimulation was performed with graded strength to differentiate between fibre groups. CVs of the same fibre groups were different in different nerves of the hindlimb. CVs for motor fibres were for the tibial nerve (Tib) 38.5±4.0 m/s (Aγ: 16.7±3.0 m/s), the sural nerve (Sur) 39.3±3.1 m/s (12.0±0.8 m/s) and the common peroneal nerve (Per) 46.7±4.7 m/s (22.2±4.4 m/s). CVs for group I afferents were 47.4±3.1 m/s (Tib), 43.8±3.8 m/s (Sur), 55.2±6.1 m/s (Per) and 42.9±4.3 m/s for the posterior biceps (PB). CVs of higher threshold afferents, presumably muscle and cutaneous, cover a broad range and do not really exhibit nerve specific differences. Ranges are for group II 22-38 m/s, for group III 9-19 m/s, and for group IV 0.8-0.9 m/s. Incontrovertible evidence was found for the presence of motor fibres in the sural nerve. The results are useful as references for further electrophysiological investigations particularly in genetically modified mice with myelination changes.
Keywords: nervové vedení; zadní končetina; myši; Hindlimb; nervový přenos; Neural Conduction; Mice; Animals; myši inbrední C57BL; neurony eferentní; zvířata; nervová vlákna; Mice, Inbred C57BL; Neurons, Efferent; neurony aferentní; Neurons, Afferent; Action Potentials; akční potenciály; Synaptic Transmission; Nerve Fibers